2016
DOI: 10.1158/1078-0432.ccr-16-1786
|View full text |Cite
|
Sign up to set email alerts
|

Human Microbiome Fusobacterium Nucleatum in Esophageal Cancer Tissue Is Associated with Prognosis

Abstract: F. nucleatum in esophageal cancer tissues was associated with shorter survival, suggesting a potential role as a prognostic biomarker. F. nucleatum might also contribute to aggressive tumor behavior through activation of chemokines, such as CCL20. Clin Cancer Res; 22(22); 5574-81. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
257
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(293 citation statements)
references
References 51 publications
7
257
1
1
Order By: Relevance
“…Interestingly and in agreement with our predictive results that fusobacteria can home-in and accumulate in high Gal-GalNAc displaying cancers, fusobacterial DNA were reported to be overabundant in pancreas (Mitsuhashi et al, 2015), breast (Hieken et al, 2016), and esophagus (Yamamura et al, 2016) adenocarcinomas and in normal and cancer stomach samples (Dicksved et al, 2009; Nardone and Compare, 2015). This, in addition to the well-known prevalence of fusobacteria in the high Gal-GalNAc -levels displaying colon cancer (Castellarin et al, 2012; Kostic et al, 2012; Abed et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…Interestingly and in agreement with our predictive results that fusobacteria can home-in and accumulate in high Gal-GalNAc displaying cancers, fusobacterial DNA were reported to be overabundant in pancreas (Mitsuhashi et al, 2015), breast (Hieken et al, 2016), and esophagus (Yamamura et al, 2016) adenocarcinomas and in normal and cancer stomach samples (Dicksved et al, 2009; Nardone and Compare, 2015). This, in addition to the well-known prevalence of fusobacteria in the high Gal-GalNAc -levels displaying colon cancer (Castellarin et al, 2012; Kostic et al, 2012; Abed et al, 2016).…”
Section: Resultssupporting
confidence: 87%
“…Another study, on the other hand, evidenced Fusobacterium nucleatum to possible mediate tumour profileration by activating several chemokines 54 . Microbial shifts may be provoked by altered microenvironments that disturb the normal salivary microbiome and, consequently, lead to a different microbial composition.…”
Section: Discussionmentioning
confidence: 98%
“…Fusobacteria was not found in the controls with normal esophagus, but was found in 10% of patients with RE and in 9% of those with Barrett's esophageal mucosa . Moreover, it has been suggested that Fusobacterium nucleatum in esophageal adenocarcinoma tissues is associated with shorter survival through the activation of chemokines and by causing aggressive tumor behavior …”
Section: Discussionmentioning
confidence: 96%